Treaty and Oath in the Ancient Near Bast: A Historian's Approach - Tadmоr, H.
ersch. 1983; in Ivrit, Engl. summary p. LXVIII; translated from the original English version in G. M. Tucker - D. A. Knight (Eds.), Humanizing America's Iconic Book: Society of Biblical Literature Centennial Addresses 1980 (Chico, California 1982).